Effect of Stress Hyperglycemia on Neurological Deficit and Mortality in the Acute Ischemic Stroke People With and Without Diabetes - Li, Jiejie; Quan, Kehua; Wang, Yilong; Zhao, Xingquan; Li, Zixiao; Pan, Yuesong; Li, Hao; Liu, Liping; Wang, Yongjun (Frontiers in Neurology, 2020)
Objective: To determine the relationship between stress hyperglycemia and prognosis of acute ischemic stroke people with and without diabetes. Methods: A subgroup of 8,622 acute ischemic stroke people with baseline levels of fasting blood glucose and HbA1c from the China National Stroke Registry II were analyzed. Stress hyperglycemia was measured by glucose/glycated hemoglobin (HbA1c) ratio, calculated by fasting blood glucose divided by HbA1c. Diabetes was diagnosed according to medical history or a HbA1c level of ≥6.5%. The outcomes included severe neurological deficit defined as modified Rankin Scale score of 3 to 5 and all-cause death at 1-year. The associations between glucose/HbA1c ratio and neurological deficit and all-cause death were analyzed via logistic regression model and Cox proportional-hazards model respectively. Subgroup analyses of participants with or without diabetes were performed separately. Results: Totally 1189 (13.7%) participants had severe neurological deficit, and 678 (7.9%) died within 1 year. Compared with the lowest quartile, the highest quartiles of glucose/HbA1c ratio were associated with elevated risk of worse neurological deficit (20.1% versus 13.0%; adjusted OR, 1.83; 95%CI, 1,31-2.54, p=0.001), and mortality (12.1% versus 6.6%; adjusted HR, 2.04; 95% CI, 1.47-2.83, p<0.0001) after adjusted for potential covariates. The association of glucose/HbA1c ratio with neurological deficit remained in the participants with and without diabetes, while it was only significant in the participants without diabetes as for the outcome of mortality. Conclusions: Stress hyperglycemia, measured by glucose/HbA1c ratio, was associated with increased risk of severe neurological deficit and mortality within 1-year in the acute ischemic stroke people.